2015
DOI: 10.7554/elife.06567
|View full text |Cite
|
Sign up to set email alerts
|

Spectrin regulates Hippo signaling by modulating cortical actomyosin activity

Abstract: The Hippo pathway controls tissue growth through a core kinase cascade that impinges on the transcription of growth-regulatory genes. Understanding how this pathway is regulated in development remains a major challenge. Recent studies suggested that Hippo signaling can be modulated by cytoskeletal tension through a Rok-myosin II pathway. How cytoskeletal tension is regulated or its relationship to the other known upstream regulators of the Hippo pathway remains poorly defined. In this study, we identify spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
134
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 64 publications
(83 reference statements)
14
134
2
Order By: Relevance
“…The forces elicited by these interactions are dynamically regulated and are especially important during processes where the cell experiences drastic changes, such as during development, cell differentiation, and regeneration [74,135138] – all processes where the Hippo pathway has been shown to be an important mediator [3,74,84,137,140]. RHO activity and the actin cytoskeletal organization are robust regulators of YAP/TAZ activity [52,139,141145]. YAP/TAZ localizes to the nucleus and is transcriptionally active in cells grown on high-rigidity substrate, under static or cyclic high tension, or in cells lacking cell–cell contact [139142,146,147].…”
Section: Yap/taz As a Signaling Networkmentioning
confidence: 99%
“…The forces elicited by these interactions are dynamically regulated and are especially important during processes where the cell experiences drastic changes, such as during development, cell differentiation, and regeneration [74,135138] – all processes where the Hippo pathway has been shown to be an important mediator [3,74,84,137,140]. RHO activity and the actin cytoskeletal organization are robust regulators of YAP/TAZ activity [52,139,141145]. YAP/TAZ localizes to the nucleus and is transcriptionally active in cells grown on high-rigidity substrate, under static or cyclic high tension, or in cells lacking cell–cell contact [139142,146,147].…”
Section: Yap/taz As a Signaling Networkmentioning
confidence: 99%
“…Spectrins were found to influence Hippo signaling, both in Drosophila and in cultured mammalian cells, in three independent studies [115-117]. Two of these suggested that Spectrins might be regulated by cytoskeletal tension, and help transduce the effects of tension onto Hippo signaling, possibly through upstream regulators of Hippo signaling including Crumbs, Merlin, and Kibra [115, 116].…”
Section: Regulation Of Hippo Signaling By Cytoskeletal Tensionmentioning
confidence: 99%
“…Two of these suggested that Spectrins might be regulated by cytoskeletal tension, and help transduce the effects of tension onto Hippo signaling, possibly through upstream regulators of Hippo signaling including Crumbs, Merlin, and Kibra [115, 116]. The other study, by contrast, reported that Spectrins influence myosin phosphorylation, and suggested that Spectrins might influence Hippo signaling by affecting actomyosin contractility [117]. Thus, while Spectrins clearly have an influence on Hippo signaling, defining the mechanism by which they regulate the Hippo network requires further study.…”
Section: Regulation Of Hippo Signaling By Cytoskeletal Tensionmentioning
confidence: 99%
“…The mechanical cues involved in the regulation of Hippo signaling include proteins that bind to intercellular junctions such as tight and adherence junctions as well as components of the cytoskeleton, including F-actin, microtubules, actomyosin, and possibly centrosomes (6166). Specifically, the interactions with centrosomes may also be relevant to the regulation of cell cycle progression by Hippo signaling.…”
Section: Regulation Of Hippo Signalingmentioning
confidence: 99%